Arctic Infrastructures: Tele Field Notes - Rafico Ruiz (communication +1, 2014)
This article contextualizes the conditions of rural “connectivity” in the Canadian Arctic. It examines the emergence of satellites, fibre optic cables, and intranets as modes of social infrastructure at the outset of the twenty-first century. At present, Nunavut, the Northwest Territories, and the Yukon are all at a complicated confluence in that their current and inadequate telecommunications infrastructures are in the process of being renegotiated, re-designed, and re-allotted across civic, governmental, and corporate interests. The article shows how it is at sites of friction that the overlapping if fading legacies of systems-based thinking are emerging: satellites orbiting over fibre optic cable lines; corporate actors competing rather than coordinating with government agencies; and neoliberal rationales of mapping, division, and speed creating disjointed local markets. More broadly, these sites also demonstrate how indigenous forms of “connection” across the globe are increasingly experiencing telecommunications’ lags and temporal disjunctures that are having very material effects on their supposedly post-colonial lives.